2007
DOI: 10.1002/ejoc.200700739
|View full text |Cite
|
Sign up to set email alerts
|

Red Pyrroloquinoline Alkaloids from the Mushroom Mycena haematopus

Abstract: Four so far unknown red alkaloid pigments, haematopodin B (1) and the mycenarubins D (3), E (5) and F (6), were isolated from fruiting bodies of Mycena haematopus. The structures of these pyrroloquinoline alkaloids were established by 2D NMR spectroscopic and MS (ESI) methods. Their absolute configurations were determined by comparison of their CD spectra with that of haematopodin (2) or mycenarubin A (4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 10 publications
1
42
0
Order By: Relevance
“…The 1 H, 13 C, COSY, HSQC, and HMBC NMR spectroscopy data of 2 closely resemble those of 1 . The most significant difference concerns C‐2 and C‐7, which indicates the presence of a quinone instead of an iminoquinone moiety; this is in agreement with the corresponding chemical shifts of 8 and 14 …”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…The 1 H, 13 C, COSY, HSQC, and HMBC NMR spectroscopy data of 2 closely resemble those of 1 . The most significant difference concerns C‐2 and C‐7, which indicates the presence of a quinone instead of an iminoquinone moiety; this is in agreement with the corresponding chemical shifts of 8 and 14 …”
Section: Resultssupporting
confidence: 80%
“…Moreover, four other red pyrroloquinoline alkaloids, named mycenarubins A ( 14 ), D ( 13 ), E ( 5 ), and F ( 6 ), were found in the fruiting bodies . Mycenarubin A ( 14 ) is also present in Mycena rosea and Mycena pelianthina , and 13 in M. pelianthina , whereas 5 and 6 have only been found in M. haematopus , to date . Herein, we describe the isolation and structural elucidation of four new pyrroloquinoline alkaloids, which have been named mycenaflavins A ( 1 ), B ( 2 ), C ( 3 ), and D ( 4 ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…P. Kumm., Peters et al (2008) found its red pyrroloquinolone alkaloid pigment to be sensitive to colour-altering structural changes, which could be inflicted by drying stress or heating, and according to Spiteller (personal communication) there are indications that this could also apply to the structurally related M. pura pigment. This corresponds with our observations of some M. pura specimens sometimes getting a dingy yellowish tinge increasing with age and/or drying.…”
Section: Differentiation In Colouration Within Calodontes?mentioning
confidence: 95%